Genome-wide association study using a Multiparent Advanced Generation Intercross (MAGIC) population identified QTLs and candidate genes to predict shoot and grain zinc contents in rice - Liu, Shilei; Zou, Wenli; Lu, Xiang; Bian, Jianmin; He, Haohua; Chen, Jingguang; Ye, Guoyou (MDPI, 2021)
Zinc (Zn) is an essential trace element for the growth and development of both humans and plants. Increasing the accumulation of Zn in rice grains is important for the world’s nutrition and health. In this study, we used a multiparent advanced generation intercross (MAGIC) population constructed using four parental lines and genotyped using a 55 K rice SNP array to identify QTLs related to Zn2+ concentrations in shoots at the seedling stage and grains at the mature stage. Five QTLs were detected as being associated with shoot Zn2+ concentration at the seedling stage, which explained 3.7–5.7% of the phenotypic variation. Six QTLs were detected as associated with grain Zn2+ concentration at the mature stage, which explained 5.5–8.9% of the phenotypic variation. Among the QTLs, qSZn2-1/qGZn2 and qSZn3/qGZn3 were identified as being associated with both the shoot and grain contents. Based on gene annotation and literature information, 16 candidate genes were chosen in the regions of qSZn1, qSZn2-1/qGZn2, qSZn3/qGZn3, qGZn7, and qGZn8. Analysis of candidate genes through qRT-PCR, complementation assay using the yeast Zn-uptake-deficient double-mutant ZHY3, and sequencing of the four parental lines suggested that LOC_Os02g06010 may play an important role in Zn2+ accumulation in indica rice.